(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The aim of this study was to evaluate the feasibility of using acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA) 3D printing filaments as materials for mammography phantom construction, comparing their attenuation properties at two different set-ups: at a Calibration Laboratory and directly to a mammography unit. The attenuation of 3D printed test phantoms of two types of common 3D printing Fused Filament Fabrication (FFF) filaments (ABS and PLA) were characterized in comparison with polymethylmethacrylate (PMMA). The measurements were carried out with standard IEC 61267 X-rays, using RQR 2-M and RQR 4-M beam qualities at the Instruments Calibration Laboratory, and then applied to a mammography unit, with measurements with 28 kVp and 35 kVp. Attenuation characteristics evaluated indicates the suitable equivalence of PLA to PMMA for 3D printing breast tissue equivalent complex phantoms. The plastic materials used in this study suggest that the FFF technique may be suitable for mammography phantom development.